1999
DOI: 10.1038/sj.onc.1202831
|View full text |Cite
|
Sign up to set email alerts
|

PED/PEA-15: an anti-apoptotic molecule that regulates FAS/TNFR1-induced apoptosis

Abstract: PED/PEA-15 is a recently cloned 15 kDa protein possessing a death eector domain (DED). In MCF-7 and HeLa cells, a ®vefold overexpression of PED/PEA-15 blocked FasL and TNFa apoptotic eects. This eect of PED overexpression was blocked by inhibition of PKC activity. In MCF-7 and HeLa cell lysates, PED/ PEA-15 co-precipitated with both FADD and FLICE. PED/PEA-15-FLICE association was inhibited by overexpression of the wild-type but not of a DED-deletion mutant of FADD. Simultaneous overexpression of PED/ PEA-15 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
150
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 155 publications
(155 citation statements)
references
References 23 publications
4
150
1
Order By: Relevance
“…32 We evaluated Casp 8 activation by western blot in U87MG-α5 high cells treated by K34c, Nutlin-3a or both. Enhanced cleaved Casp 8 was detected only in cells treated with both drugs (Figure 3f).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…32 We evaluated Casp 8 activation by western blot in U87MG-α5 high cells treated by K34c, Nutlin-3a or both. Enhanced cleaved Casp 8 was detected only in cells treated with both drugs (Figure 3f).…”
Section: Resultsmentioning
confidence: 99%
“…32 PEA-15 can be phosphorylated on ser116 by AKT and on ser104 by protein kinase C leading to different functional implications. 40 In fact, unphosphorylated PEA-15 acts as a tumor suppressor by sequestering extracellular signal-regulated kinase in the cytoplasm and thus inhibits proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, active caspase-8 cleaves and activates the effector protein caspase-3 (Stennicke et al, 1998) to cleave various substrates, including PARP, a-fodrin and lamin A (Nicholson et al, 1995;Oliver et al, 1998). It has been reported that the oncoprotein MUC1 and PEA-15 can block death receptor-mediated apoptosis by binding to the DED of FADD and inhibiting procaspase-8 recruitment (Condorelli et al, 1999;Agata et al, 2008). Similar to these proteins, DJ-1 bound directly to the DED of FADD (Figure 5b), which is required for its interaction with pro-caspase-8, to compete with caspase-8 to bind to FADD (Figure 5c).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PEA15 exerts a wide anti-apoptotic action. It binds Fas-associated death domain (FADD) and caspase-8, thereby protecting against cytokine-induced apoptosis [9][10][11]. PEA15 also binds to Omi/HtrA2 to inhibit apoptosis triggered by stress and physical agents [12].…”
Section: Introductionmentioning
confidence: 99%